THE EFFECT OF FEAR OF MISSING OUT (FOMO) AS AN INDICATOR OF VIRAL PRODUCT PURCHASE DECISIONS BY HEDONICALLY ORIENTED STUDENTS - Shally Ruth Yuliana Manik; Hadijah Zoya; Amelia Situmorang; Tria Anggina; Rafael Krismahendra Panjaitan; Andi Taufiq Umar (RADJA PUBLIKA, 2025)
This study aims to examine the influence of Fear of Missing Out (FOMO) and hedonic orientation on the purchasing decisions of viral products among college students. The main issue raised is how the psychosocial dynamics of college students in the digital era affect impulsive consumption patterns, especially when exposed to viral trends on social media. This study uses a quantitative explanatory approach with a questionnaire survey method supported by literature studies. The research sample consists of active social media students who have purchased viral products. The results of the study show that both FOMO and hedonic orientation have a significant simultaneous influence on purchasing decisions of viral products, with hedonic orientation having a greater influence than FOMO. This finding is different from several previous studies that highlight the dominance of FOMO. This study confirms that college students' consumption motivation is more influenced by the search for pleasure and emotional satisfaction than simply anxiety about being left behind. The implication of these results is the need for a digital marketing strategy that emphasizes the emotional experience aspect, as well as the development of rational consumption literacy for the younger generation amidst the ever-growing flow of viral trends.